2014
DOI: 10.1016/j.jchromb.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic determination of low-molecular mass unsaturated aliphatic aldehydes with peroxyoxalate chemiluminescence detection after fluorescence labeling with 4-(N,N-dimethylaminosulfonyl)-7-hydrazino-2,1,3-benzoxadiazole

Abstract: A highly sensitive, selective and reproducible chromatographic method is described for determination of low-molecular mass unsaturated aliphatic aldehydes in human serum. The method combines fluorescent labeling using 4-(N,N-Dimethylaminosulfonyl)-7-hydrazino-2,1,3-benzoxadiazole with peroxyoxalate chemiluminescence. The derivatives were separated on a reversed-phase column C8 isocratically using a mixture of acetonitrile and 90mM imidazole-HNO3 buffer (pH 6.4, 1:1, % v/v). The calibration ranges were: 20-420n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…18 With respect to the involvement of acrolein in diabetes, acrolein was reportedly increased in the serum of patients with diabetes. 19 It was also shown that the urinary level of acrolein was higher in type 2 diabetes patients than in individuals without diabetes. 18 By contrast, little is known about the role of acrolein in ocular diseases, including DR.…”
Section: Discussionmentioning
confidence: 98%
“…18 With respect to the involvement of acrolein in diabetes, acrolein was reportedly increased in the serum of patients with diabetes. 19 It was also shown that the urinary level of acrolein was higher in type 2 diabetes patients than in individuals without diabetes. 18 By contrast, little is known about the role of acrolein in ocular diseases, including DR.…”
Section: Discussionmentioning
confidence: 98%
“…The regression equation (mean ± standard error, n = 3) was y = (0.895 ± 0.038) x + 0.066 ± 0.030, where y is the peak area ratio and x is the concentration of acrolein (μ M ). The sensitivity of the proposed method was 100 times greater compared with time‐resolved fluorescence assay (Togashi et al ., ), 15–20 times graeter compared with HPLC with electrochemical detection (Casella and Contursi, , ) and 4–10 times greater compared with HPLC with fluorescence detection (Ali et al ., ; Bohnenstengel et al ., ; Paci et al ., ). Additionally, the sensitivity was almost comparable to that of GC‐MS (Osório and de Lourdes Cardeal, ).…”
Section: Resultsmentioning
confidence: 99%
“…To date, several methods have been developed for the determination of acrolein using time-resolved fluorescence assay (Togashi et al, 2010), gas chromatography with mass spectrometry (GC-MS; Osório and de Lourdes Cardeal, 2011), high-performance liquid chromatography (HPLC) with fluorescence detection (Ali et al, 2014;Bohnenstengel et al, 1997;Paci et al, 2000), electrochemical detection Contursi, 2004, 2014) and liquid chromatography with tandem mass spectrometry (LC-MS/MS; Andreoli et al, 2003). In these methods, derivatization reactions were frequently adopted for the determination of acrolein in order to improve detectability and stability (Shibamoto, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new chromatographic method for detecting low molecular mass aldehydes in human serum through a combination of fluorescence labelling and PO‐CL was published by Ali et al . Cellular oxidative stress can lead to lipid peroxidation of unsaturated fatty acids in cell membranes, which produces low molecular mass aldehydes which are cytotoxic and react with DNA .…”
Section: Application Of Peroxyoxalate CL Read‐outmentioning
confidence: 99%